The Potential Association of Delayed T Lymphocyte Reconstitution Within Six Months Post-Transplantation With the Risk of Cytomegalovirus Retinitis in Severe Aplastic Anemia Recipients - Mo, Wenjian; Chen, Xiangting; Zhang, Xu; Wang, Shunqing; Li, Ling; Zhang, Yuehong (Frontiers in Cellular and Infection Microbiology, 2022)
Background Delayed immune reconstitution after allogeneic hematopoietic stem cell transplantation (HSCT) is significantly associated with cytomegalovirus (CMV) infection. The aim of this study was to observe the recovery trend of peripheral lymphocyte subsets and immunoglobulins in HSCT recipients who developed CMV retinitis (CMVR). Methods We identified 37 CMVR cases and 303 non-CMVR controls in this case-control study from a database of 404 consecutive severe aplastic anemia patients who received allogeneic HSCT at a single center between 2015 and 2020. We analyzed the transplant outcomes and immune reconstitution principles with a focus on lymphocyte CD series and immunoglobulin series within the first year post-HSCT. Results Thirty-seven patients (55 eyes) were diagnosed with CMVR, with a mean onset time of 155 days post-HSCT. Among the 37 patients, one never had CMV detected in his blood but had a high CMV load in his intraocular fluid at the time of CMVR diagnosis. In the controls, 195 had CMV viremia and 108 did not. Compared with controls, CMVR cases had a longer duration of CMV viremia and a higher peak number of CMV load. T lymphocyte subsets including CD3, CD4 and CD8 were significantly lower in CMVR cases within six months after HSCT (all p < 0.05). Immunoglobulins also showed a slower recovery trend in CMVR cases. The recovery of B lymphocytes and natural killer cells exhibited no significant differences between the two groups. Conclusions It is not enough to develop fundus screening strategies by merely relying on the CMV serostatus of recipients. Dynamic and continuous monitoring of T lymphocyte subsets, especially within six months post-HSCT, as well as serum immunoglobulin levels, can provide assistance with screening program of CMVR in HSCT recipients with severe aplastic anemia.